Chemotherapy for intracranial ependymoma in adults. Issue 1 (December 2016) - Gramatzki, Dorothee; Roth, Patrick; Felsberg, Jörg; Hofer, Silvia; Rushing, Elisabeth; Hentschel, Bettina; Westphal, Manfred; Krex, Dietmar; Simon, Matthias; Schnell, Oliver; Wick, Wolfgang; Reifenberger, Guido; et al.
Abstract Background Ependymal tumors in adults are rare, accounting for less than 4 % of primary tumors of the central nervous system in this age group. The low prevalence of intracranial ependymoma in adults limits the ability to perform clinical trials. Therefore, treatment decisions are based on small, mostly retrospective studies and the role of chemotherapy has remained unclear. Methods We performed a retrospective study on 17 adult patients diagnosed with intracranial World Health Organisation grade II or III ependymoma, who were treated with chemotherapy at any time during the disease course. Benefit from chemotherapy was estimated by applying Macdonald criteria. Progression-free (PFS) and overall survival (OS) were calculated from start of chemotherapy, using the Kaplan-Meier method. Results Eleven patients had supratentorial and 6 infratentorial tumors. Ten patients were treated with temozolomide (TMZ), 3 with procarbazine/lomustine/vincristine (PCV), 3 with platinum-based chemotherapy and 1 patient received epirubicin/ifosfamide. Response rates were as follows: TMZ 8/10 stable disease; PCV 3/3 stable disease; platinum-based chemotherapy 1/3 partial response; epirubicin/ifosfamide 1/1 complete response. PFS rates at 6, 12 and 24 months were 52.9, 35.3 and 23.5 %. OS rates at 6, 12 and 24 months were 82.4, 82.4 and 70.1 %. There was no indication for a favourable prognostic role ofO 6 -methylguanyl-DNA-methyltransferase (MGMT ) promoter methylation which was detected in 3/12 investigated tumors. Conclusions Survival outcomes in response to chemotherapy in adult intracranial ependymoma patients vary substantially, but individual patients may respond to any kind of chemotherapy. There were too few patients to compare survival data between chemotherapeutic subgroups.